Pós-colheita de morangos Camarosa e pêssegos Eldorado produzidos em sistema orgânico e convencional armazenados em atmosfera controlada. - Schünemann, Ana Paula Pereira (2009)
The objective of this study was to evaluate the effect of controlled atmosphere (CA) on the physico-chemical and sensory quality strawberry Camarosa‟ and peach 'Eldorado', produced under conventional (CS) and organic (OS) system during the storage. We applied the statistical technique of principal component analysis (PCA) between the sensory variables in strawberry Camarosa‟ and peach 'Eldorado', to select the variables most representative of the variability of the data and characterize homogeneous groups of samples as storage system under refrigeration or under different conditions of CA and production system SC and SO. The strawberries were stored at a temperature of 1.5 º C RH 90-95%, and made the following treatments: cold storage (CS) - 21% O2 and 0.03% CO2, 4% O2 + 5% CO2 (AC1) 4% O2 + 10% CO2 (AC2). The fruits were kept under storage for a period of 3, 6 and 9 days to 1.5 ° C plus one day of simulated commercialization (SC) at 20 ° C. The peaches were stored at a temperature of 1.5 º C relative humidity of 90-95%, and made the following treatments: control 21% O2 + 0.03% CO2 (AR), 2% O2 + 5% CO2 (AC1), 2% O2 + 10% CO2 (AC2), 2% O2 + 15% CO2 (AC3). The fruits were stored for a period of 15, 30 and 45 days at 1.5 ° C over three days in SC at 20 ° C. A completely randomized design was used for the physic-chemical analyzes, and for the sensory analysis a randomized block design; each judger was considered as a replication. Data were submitted to analysis of variance, and for mean comparison it was applied the Tukey test (P <0.05). AC with 4% O2 and 5% CO2 was effective in preserving the physical, chemical and sensory strawberries Camarosa‟ up to nine days + one day of the SC produced an CS and up to 6 days to the OS. Using cold AR be stored up to this period was lower, without significant losses in firmness, weight loss and significant changes in the attributes of appearance, flavor and texture. The fruits stored in AR In peaches 'Eldorado', in general, the fruit was change the characteristics of flavor, texture and appearance, and the treatments containing 2% O2 and 10% CO2 and 2% O2 and 15% CO2 preserved the physical-chemical and sensory up to 30 days in CS and 15 days in the OS. In AR this period was less than 15 days, without significant losses in sensory quality. Furthermore, the 45 days treatments were altered would not permit evaluation of flavor. The PCA was valid to discriminate the proxy variables and characterize homogeneous groups.